MR Imaging of Syringomyelia and Hydromyelia - Lee, Benjamin C. P.; Zimmerman, Robert D.; Manning, John J.; Deck, Michael D. F. (American Journal of Neuroradiology, 1985)
The relative effectiveness of plain computed tomography (CT), metrizamide CT, conventional myelography, and magnetic resonance (MR) imaging was compared for the examination of cystic spinal cord lesions. Intramedullary cavities in 18 patients were demonstrated by MR imaging: cavities were uncomplicated in 13 patients, associated with spinal tumors in two, and studied after occipital craniectomy for treatment of Chiari malformation and syringomyelia in two. Cavities were shown by MR imaging in all enlarged spinal cords, but a cavity was shown in only one of four small cords. The rostral limits of the cavities were demonstrated better than were the caudal extensions. Ventricular communication was not demonstrated. Chiari malformation was shown only in cavities that did not involve the medulla. Syringes associated with tumor were indistinguishable from uncomplicated cavities, but the tumor had abnormal signal on long spin-echo sequences in two cases. Cystic cord tumor (one case) had an inhomogeneous appearance. Caudal displacement of the cerebellar hemisphere through the surgical defect associated with compression of the fourth ventricle was shown in two cases after posterior fossa craniectomy. Thirteen patients were studied with metrizamide CT also. MR imaging proved to be as accurate as metrizamide CT in the diagnosis of intramedullary cavities that result in spinal cord enlargement, but it was less sensitive in detecting cavities within normal-sized or diminished spinal cords. It had the advantage that tumor tissue could be distinguished from associated syrinx cavities by differences in signal characteristics; and cerebellar ectopia was evaluated easily on sagittal MR views.